Model Evaluasi Dosen Metodologi Ekonomi Islam Oleh Mahasiswa Selama Pandemi Covid 19 - Muizzudin Udin (Thawalib: Jurnal Kependidikan Islam, 2021)
The research is aimed at evaluating the lecturer performance in teaching the methodology of Islamic economics based on the students’ observation during the online course as the effect of COVID 19. The measurement of the performance refers to the concept of satisfaction related to the educational service by comparing the performance to the expectation adopted from Parasunaman’s five quality dimension: tangible, reliability, responsiveness, assurance, and empathy. The data is collected from the questionnaire. The descriptive quantitative research is used to map the strengths and weaknesses in four classifications: first, what aspects a lecturer should prioritize because the lecturer performance is low and the student expectation is high; second, what aspects a lecturer should maintain because the lecturer performance is in line with the student expectation; third, what aspects a lecturer should maintain but think again about weighting them because the lecturer performance is low and the student expectation is also low; fourth, what aspects a lecturer should reduce their emphasis because the lecturer performance is high but the student expectation is low. The result shows that with the four classification the lecturer performance related to the service quality can be managed well.